An effect of hydrogenation on the photoemission of amorphous SiCN films. (5th February 2022) - Ivashchenko, V.I.; Porada, O.K.; Kozak, A.O.; Manzhara, V.S.; Sinelnichenko, O.K.; Ivashchenko, L.A.; Shevchenko, R.V.
Abstract: The structure, chemical bonding and photoemission of amorphous hydrogenated silicon carbonitride (a-SiCN:H) films deposited by plasma-enhanced chemical vapor deposition (PECVD) using hexamethyldisilazane as a main precursor at different hydrogen flow rates are studied. Film properties are characterized by X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, X-ray photoelectron spectroscopy (XPS), absorption optical spectra and photoluminescence (PL). The photoluminescence spectra were presented by four photoemission bands centered at 441–451, 489–496, 530–535 and 577–601 (in nm). To explain structural and photoluminescence properties of the deposited films, first-principles molecular dynamics simulations of un-hydrogenated and hydrogenated silicon carbonitride samples were carried out. Based on experimental and theoretical results a possible explanation of the photoemission of the deposited films and its evolution with increasing hydrogen flow rate was done. Highlights: Photoluminescence spectra of a-SiCN:H films were measured depending on hydrogen flow. Photoemission was quenched with increasing hydrogen flow. First-principles calculations of hydrogenated and non-hydrogenated SiCN were done. A possible origin of photoemission suggests the recombination between the band, their tails and gap states. An effect of the non-hydrogenated and hydrogenated networks and local atomic surrounding on photoemission was analyzed.